Effects of sex and retention interval on the retrieval and extinction of auditory fear conditioning - Schoenberg, Hannah L.; Blanchard, Madeleine; Cheng, Han Yin; Winterbauer, Neil E.; Toufexis, Donna J.; Todd, Travis P. (Frontiers in Behavioral Neuroscience, 2022)
Fear memory retrieval is relevant to psychiatric disorders such as post-traumatic stress disorder (PTSD). One of the hallmark symptoms of PTSD is the repeated retrieval and re-experiencing of the initial fear memory even long after the traumatic event has occurred. Women are nearly twice as likely to develop PTSD following a trauma than men, thus sex differences in the retrieval of fear memories is highly relevant for understanding the development and maintenance of PTSD. In the current study, we aimed to examine sex differences in the retrieval and extinction of either recent or remote fear memories. To do so, we conditioned male and female rats either 1 day (recent) or 28 days (remote) prior to testing retrieval and extinction. While there was no effect of sex or retention interval on initial retrieval, we found that remotely-conditioned females exhibited higher rates of freezing than remotely-conditioned males in later retrieval/extinction sessions, suggesting a sex difference in the retrieval and/or extinction of remote, but not recent, fear memories. Overall, these results are the first to demonstrate a sex difference in the extinction of remote fear memory, and this may contribute to the differential expression of fear-related disorders like PTSD in men and women.